2012
DOI: 10.1371/journal.pone.0050851
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular Chaperone HSPA2 Plays a Key Role in Regulating the Expression of Sperm Surface Receptors That Mediate Sperm-Egg Recognition

Abstract: A common defect encountered in the spermatozoa of male infertility patients is an idiopathic failure of sperm–egg recognition. In order to resolve the molecular basis of this condition we have compared the proteomic profiles of spermatozoa exhibiting an impaired capacity for sperm-egg recognition with normal cells using label free mass spectrometry (MS)-based quantification. This analysis indicated that impaired sperm–zona binding was associated with reduced expression of the molecular chaperone, heat shock 70… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
121
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 124 publications
(132 citation statements)
references
References 44 publications
10
121
0
1
Order By: Relevance
“…Several of these RHOX-regulated genes have been shown to have crucial roles in human male reproduction. For example, idiopathic infertile men who completely lack HSPA2 in their sperm exhibit impaired fertilizing ability (31,34) and reduced expression of HSPA1A in ejaculated sperm has been implicated in the pathogenesis of male infertility (35).…”
Section: Discussionmentioning
confidence: 99%
“…Several of these RHOX-regulated genes have been shown to have crucial roles in human male reproduction. For example, idiopathic infertile men who completely lack HSPA2 in their sperm exhibit impaired fertilizing ability (31,34) and reduced expression of HSPA1A in ejaculated sperm has been implicated in the pathogenesis of male infertility (35).…”
Section: Discussionmentioning
confidence: 99%
“…Heat shock protein member A2 (HSPA2) is present in the human spermatozoa and binds with arylsulfatase A (ARSA) and sperm adhesion molecule 1 (SPAM1) (Redgrove et al 2012, 2013, Bromfield et al 2016. Both ARSA and SPAM1 are detected in the rabbit and mouse oviduct (Vitaioli et al 1996, Griffiths et al 2008.…”
Section: Fertilizationmentioning
confidence: 99%
“…Other HSPs were observed in this study, of which we highlight the conserved Heat Shock-Related 70 kDa Protein 2 (HSPA2). HSPA2 was suggested as an important protein for sperm-egg recognition and fusion during fertilization [54]. Lima et al [55] demonstrated that adolescents with varicocele and unaltered semen when compared to age-matched controls presented an overexpression in the HSPA2 gene, not observed in adolescents with varicocele and altered semen.…”
Section: Conserved Functionsmentioning
confidence: 99%